Epidemiological factors associated with HBV infection and uptake of testing in south west region of Cameroon: What can be done to scale up HBV testing in our setting? - Henry Dilonga Meriki; Kukwah Anthony Tufon; Teuwafeu Denis Georges; Ngomba Divine Martin Mokake; Ronald Mbua Gobina; Nyeke James Tony; Tebit Emmanuel Kwenti; Ayah Flora Bolimo; Malika Esembeson; Nkouonlack Cyrille; Fokam Djike Puepi Yolande; Iyah Rebecca Itoe; et al. (Public Library of Science (PLoS), 2022)
Hepatitis B infection affects millions of people globally, partly due to its high degree of transmissibility and asymptomatic nature. This study was aimed at identifying prevailing epidemiological factors associated with HBV infection and testing uptake in the South West region of Cameroon. This hospital-based case-control study enrolled HBV infected participants and "healthy" controls ≥18 years old. Venous blood collected from participants was used to conduct HBV panel test (HBsAg, anti-HBs, HBeAg, anti-HBe, anti-HBc). Data on demographic and behavioral risk factors as well as reasons for taking the HBV test for the first time were collected using a questionnaire. A total of 424 participants were enrolled (212 "healthy" controls and 212 HBV infected cases). Male sex (odds ratio [OR] = 2.08, p = 0.010), ≤ secondary education level (OR = 4.83, p<0.001), low-income level (OR = 3.79, p<0.001), rural settlement (OR = 2.17, p = 0.031), history of sexually transmitted infections (STI) (OR = 4.24, p<0.001) and ignorance of sexual partners HBsAg status (OR = 2.70, p = 0.003) all had an independent and significant association with HBV infection. Top 3 reasons for doing HBsAg test were free screening (40.3%), blood donation (15.0%) and administrative requirements (14.9%). HBV testing uptake and early detection can be improved if more sensitization and free/opportunistic screenings are implemented. A significant drop in the cost of HBV test could encourage more people to get tested.